2015
DOI: 10.1111/jasp.12332
|View full text |Cite
|
Sign up to set email alerts
|

Colorblind or colorful? How diversity approaches affect cultural majority and minority employees

Abstract: We examined how perceived organizational diversity approaches (colorblindness and multiculturalism) relate to affective and productive work outcomes for cultural majority and minority employees. Using structural equation modeling on data collected in a panel study among 152 native Dutch majority and 77 non-Western minority employees, we found that perceptions of a colorblind approach were most strongly related to work satisfaction and perceived innovation for majority members, while perceptions of a multicultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 61 publications
4
63
2
2
Order By: Relevance
“…Two main ideological perspectives have been proposed as the most suitable ways to manage diversity and reduce prejudice: (a) the multicultural perspective, which regards the acknowledgment and social validation of the existence of different groups as critical to attain equality and diversity in society (Deaux & Verkuyten, ; Plaut, ); and (b) the colorblind perspective, which argues that the best way to achieve equality involves downplaying group distinctions, avoiding any reference to social categories, and treating people as unique individuals (Apfelbaum, Norton, & Sommers, ). Previous studies have compared these two perspectives (see Rattan & Ambady, , for a review); most of the findings of such studies confirm that the multicultural perspective yields more positive results, in terms of minimizing prejudice, and promoting positive intergroup behavior, as well as support for public policies that favor minorities or that improve outcomes for minority members of work‐related organizations (Jansen, Vos, Otten, Podsiadlowski, & Van der Zee, ; Richeson & Nussbaum, ; Wolsko et al, ). Moreover, the research has demonstrated that the multicultural perspective is effective at buffering the negative effects related to the salience of categorization (Costa‐Lopes, Pereira & Judd, ).…”
Section: The Multicultural Perspectivementioning
confidence: 83%
“…Two main ideological perspectives have been proposed as the most suitable ways to manage diversity and reduce prejudice: (a) the multicultural perspective, which regards the acknowledgment and social validation of the existence of different groups as critical to attain equality and diversity in society (Deaux & Verkuyten, ; Plaut, ); and (b) the colorblind perspective, which argues that the best way to achieve equality involves downplaying group distinctions, avoiding any reference to social categories, and treating people as unique individuals (Apfelbaum, Norton, & Sommers, ). Previous studies have compared these two perspectives (see Rattan & Ambady, , for a review); most of the findings of such studies confirm that the multicultural perspective yields more positive results, in terms of minimizing prejudice, and promoting positive intergroup behavior, as well as support for public policies that favor minorities or that improve outcomes for minority members of work‐related organizations (Jansen, Vos, Otten, Podsiadlowski, & Van der Zee, ; Richeson & Nussbaum, ; Wolsko et al, ). Moreover, the research has demonstrated that the multicultural perspective is effective at buffering the negative effects related to the salience of categorization (Costa‐Lopes, Pereira & Judd, ).…”
Section: The Multicultural Perspectivementioning
confidence: 83%
“…Indeed, "One powerful tool at organizations' disposal is their ability to shape the cultural context of the workplace (Avery et al 2007;Jansen et al 2015;Wilton et al 2015)-a key component of which is how diversity and social group differences are discussed . .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are important for individuals, organizations, and broader society because the diversity perspective of an executive determines how strongly minorities and majorities experience inclusion in their workplace, as they can influence the likelihood of fault lines and conflict and increase cooperation and innovation (Ely & Thomas, 2001;Jansen et al, 2016;Sessler Bernstein & Bilimoria, 2013 (Kristof, 1996), companies should devote extra effort to onboarding to help candidates be effective in an environment that does not match their values or attitudes.…”
Section: Managerial Implicationsmentioning
confidence: 96%
“…In this line of research, Thomas and Ely () introduced diversity perspectives, that is, the “philosophy” or “approach” to diversity, as a factor influencing an organization's ability to leverage the potential of a diverse workforce and diminish potential negative effects. Diversity perspectives, which can be held by organizations, groups, or executives, shape organizational processes and policies and influence whether employees feel respected and valued at their workplace and how people perceive the meaning of diversity at work (Ely & Thomas, ; Jansen, Vos, Otten, Podsiadlowski, & van der Zee, ; Sessler Bernstein & Bilimoria, ). Thomas and Ely's work was among the main drivers shifting the focus of diversity literature from equal employment and minority rights to finding value in diversity and ensuring the inclusion of diverse employees.…”
Section: Introductionmentioning
confidence: 99%